Malate-aspartate shunt in neuronal adaptation to ischemic conditions: Molecular-biochemical mechanisms of activation and regulation - Belenichev, I. F.; Kolesnik, Yu. M.; Pavlov, S. V.; Sokolik, E. P.; Bukhtiyarova, N. V.; Бєленічев, Ігор Федорович; Колесник, Юрій Михайлович; Павлов, Сергій Васильович; Соколик, Олена Петрівна; Бухтіярова, Ніна Вікторівна (Pleiades Publishing, 2012)
Acute or chronic brain ischemia induces a cascade of pathobiochemical reactions that finally result in the development of focal neurological deficit, dyscirculatory encephalopathy, or the death of a patient. We studied the effects of ischemia at different time points, including 1, 6, 24, 48, 72, and 120 h, and 21 days. During the period of the strongest ischemia-induced disturbances (24–72 h), we found lactate over-production associated with inhibition of hexokinase, an enzyme that catalyzes the first “trigger” reaction of glycolysis. An increase in the malate content associated with increasing activities of mitochondrial and cytosolic malate dehydrogenases within the first hours of cerebral ischemia indicates the activation of the malateaspartate shuttle, which is responsible for the transportation of reduced equivalents to mitochondria. The inhibition of malate production and activity of NAD-dependent malate dehydrogenase correlates with a decrease in the contents of ATP, HSP70, and hypoxia-induced factor-1a (HIF-1a) and the severity of neurological disturbances. We believe that in response to brain ischemia, HIF-1a is expressed, which induces compensatory mechanisms of energy production.
Keywords: brain ischemia; compensatory shunts of energy production; mitochondrial-cytosolic energy transmission; heat shock proteins